Fairness, transparency and attitude towards tax evasion amongst owners of SMEs / Susan Hydra Sikayu ... [et.al.] - Sikayu, Susan Hydra; Rahmat, Mariam; Chan, Ai Nyet (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Tax evasion amongst small and medium-sized enterprises (SMEs) is a global concern. While the social-psychological aspect has been explored, its influence on tax evasion in SMEs is still inconclusive. This study examines the effect of fairness and transparency on the attitude towards tax evasion amongst the owners of SMEs. A mixed-mode survey was used in obtaining data from four populous divisions of Sarawak, Malaysia. Random sampling was employed in selecting the potential respondents from the service sector. Data from 91 useable questionnaires were analysed using Smart-PLS 3.0. The results revealed that distributive fairness and distributive fiscal transparency have significant negative effects on SME owners’ attitudes towards tax evasion. On the other hand, general fairness and informational transparency were insignificant. These findings may benefit the tax authority and policymakers in formulating appropriate strategies to curb erosion of income tax revenue from tax evasion.